Strategi Humas Pt. Hutama Karya (Persero)Dalam Meningkatkan Pemahaman Masyarakat Dalam Penggunaan E-Toll Card di Ruas Tol Akses Tanjung Priok (ATP) - Diana Prihadini; Rofian Dedi Susanto; Restu Ikhtiar (LUGAS Jurnal Komunikasi, 2022)
The purpose of this study was to analyze the PR strategy of PT. Hutama Karya (Persero) in increasing public understanding in the use of e-Toll Cards on the Tanjung Priok Access (ATP) toll road, the obstacles that arise and the efforts made to overcome these obstacles. The method used in this research was descriptive qualitative method with data collection through observation, in-depth interviews, and literature study. This study also used Ruslan's theory of communication strategy, which includes 5 (five) components, namely: operational strategy, persuasive and educative approach, social responsibility approach of public relations, cooperative approach, and coordinating and integrative approach. It is very important to make a public relations strategy so that the expected goals and objectives can be achieved. The results of this study indicate that the PR strategy of PT. Hutama Karya (Persero) in increasing public understanding in the use of e-Toll Cards on the Tanjung Priok Access (ATP) toll road is to conduct a persuasive and educative campaign to toll road users. This effort has proven successful, as seen from theincreasing use of E-toll Cards on the Tanjung Priok Access toll road.